Μελέτη ενζυμικού πολυμερισμού και μεταπολυμερισμού μάζας με στόχο την παραγωγή πολυ(ηλεκτρικού βουτυλεστέρα) - Ρηγοπούλου, Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Σύνθεσης και Ανάπτυξης Βιομηχανικών Διαδικασιών (IV). Εργαστήριο Τεχνολογίας Πολυμερών, 2017)
The main objective of this diploma thesis is to study an alternative process for the production of poly(butylene succinate) (PBS) which is divided in two stages. The first stage involves the enzymatic prepolymerization of 1,4-butanediol and diethyl succinate, two monomers which may be derived from renewable raw materials. The second step concerns the bulk post-polymerization of the products of enzyme prepolymerization in order to improve the properties of the final biodegradable polymer. The enzymes that are tested for their catalytic activity are a commercially available immobilized lipase B of Candida antarctica (CALB, Novozym 435, N435) and the cross-linked cutinase aggregates (CLEAS) of Fusarium oxysporum (FoCut5a), which was prepared in the framework of this study at the Laboratory of Biotechnology, NTUA. Regarding the enzyme prepolymerization step, the suitability of two different solvents, as well as the bulk polymerization system are examined. Furthermore, the effect of temperature on the performance of the reactions and the properties of the products are studied. As far as the post-polymerization process is concerned, two thermally distinct stages are applied and the appropriate time of each stage is investigated. One of the sizes calculated to evaluate the reactions is the mass yield of the process. The reaction products of both enzymatic prepolymerization and post-polymerization are analyzed by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) to identify their thermal properties. Magnetic Nuclear Resonance (NMR) spectroscopy was also used to identify the products and calculate the number average molecular weight. Finally, solution viscometry was used to determine the weight-average molecular weight of the post-polymerization products. The purpose of this thesis is to develop an alternative process for the prepolymerization and post-polymerization of the aliphatic polyester PBS by biocatalyzing and mild-temperature conditions. Tests were performed on a small laboratory scale (about 150 mg of product) by simple methods and relatively volatile solvents to identify the appropriate conditions. Thus, it is finally managed to present an integrated method of producing pure low molecular weight PBS (Mw ≈ 5000 g/mol), a biodegradable polymer which can be produced from renewable raw materials and with potential biomedical applications. The use of N435 led to production of PBS of low molecular weight (Mn ≈ 1500 − 3900 g/mol) with yields and thermal properties not significantly dependent on the reaction temperature or the solvent used. The use of cutinase led to the formation of PBS dimers and trimers, regardless of the activity of the enzyme. Finally, the two-step bulk post-polymerization of an enzymatically produced prepolymer managed to increase its weight-average molecular weight by about 60 % (from Mw = 1967 g/mol to Mw = 4530 g/mol) and to improve its thermal properties.